COMPARATIVE STUDY OF LATERAL INTERNAL ANAL SPHINCTEROTOMY VERSUS BOTOX INJECTION IN PATIENTS OF ANAL FISSURE (The Research of Medical Science Review, 2025)
Background: Chronic anal fissures are a common anorectal condition, causing significant pain and discomfort, particularly during or after bowel movements. Conventional treatments, including lateral internal anal sphincterotomy (LIAS) and botulinum toxin (Botox) injection, are widely used to manage chronic anal fissures. While both treatment modalities aim to reduce pain and promote healing, their comparative effectiveness remains under investigation. Objective: This study aimed to compare the healing rates, pain relief, fissure recurrence, complications, and side effects of LIAS versus Botox injection in the treatment of chronic anal fissures. Study Design and Setting: A retrospective comparative study was conducted at Shaikh Zayed Hospital Lahore from October 2024 to March 2025. Methodology: The study included 120 patients with chronic anal fissures who were assigned to receive either LIAS (n=60) or Botox injection (n=60). Patients were assessed for fissure healing, pain relief, and complications at 1-week, 1-month, and 3-month follow-up visits. Healing was assessed clinically, and pain levels were measured using the Visual Analog Scale (VAS). Complications such as incontinence, mild weakness, and pain at the injection site were also recorded. Statistical analysis was performed using SPSS software, with comparisons made using chi-square and t-tests. Results: At 3 months, 90% of LIAS patients had healed, compared to 73% of Botox patients. The LIAS group showed a greater reduction in pain (VAS scores of 1.5 ± 1.0) compared to the Botox group (VAS scores of 2.0 ± 1.2). The recurrence rate was lower in the LIAS group (5%) compared to the Botox group (17%). Conclusion: LIAS demonstrated higher healing rates, greater pain relief, and a lower recurrence rate compared to Botox in the treatment of chronic anal fissures. Both treatments were generally safe, but Botox had a higher incidence of side effects.